PRELIMINARY PHYTOCHEMICAL ANALYSIS AND LARVICIDAL ACTIVITY OF EDIBLE FERN (Diplazium esculentum (Retz.) Sw.) EXTRACT AGAINST Culex - Halimatussakdiah Halimatussakdiah; Ulil Amna; Puji Wahyuningsih (Universitas Syiah Kuala, 2018)
Mosquito is one of insects spreading the vector of serious diseases to human being through its bite such as Culex which spreads the vector of filariasis and brain inflammatory diseases. Some people have used plants as insecticides traditionally, such as fern (Diplazium esculentum (Retz.) Sw.). D. esculentum (Retz.) Sw. popularly known as edible fern which almost all Asian people, especially Indonesian consumed it as vegetable, and some people also used it for medicinal purposes. This study was performed to investigate the secondary metabolites from D. esculentum leaves and its larvicidal activity against Culex. The phytochemical screening was undertaken on the leaves and methanol extract of D. esculentum, the results showed the presence of alkaloids, steroids, phenols, and tannins on leaves, while methanol extract exhibited existence of steroids, saponins, phenols and tannins. Investigation of larvicidal activity of methanol extract was carried out against Culex larvaes for various concentrations which observed for 48 hours. Percentage of mortality was analyzed statistically using Bill Test method that showed active larvicidal activity with a LC50 value of 149.279 ppm. This study indicates that fern plant have the potential as larvicidal against Culex and need to perform the further research to develop the new natural insecticides.